Landscapes of Despair : From Deinstitutionalization to Homelessness - Dear, M. J. (Michael J.); Wolch, Jennifer R. (Book collections on Project MUSE., 1987)
Michael Dear and Jennifer Wolch examine the emergence of urban ghettos of the socially dependent--an unforeseen "solution" to the problem of developing community-based care for a variety of service-dependent groups, including the mentally and physically disabled, ex-offenders, and addicts. Based on detailed case studies drawn from several cities in Canada and the United States, Landscapes of Despair is a comprehensive analysis of these ghettos.Originally published in 1987.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.